Key influencers in Burkina Faso's poultry management: Insights from systems mapping and network analysis - Boz, Z.; Dione, Michel M.; Alders, R.; Kagambèga, A.; Knight-Jones, Theodore J.D.; Ilboudo, Guy S.; Ouedraogo, Brice; Ima-Ouoba, S.; Ganser, S. (International Livestock Research Institute, 2024)
Background: Effective management of livestock systems is essential for optimizing productivity and sustainability. This research utilizes systems mapping and network analysis to identify pivotal elements within poultry management concepts. The aim is to ascertain nodes that exert significant influence on operational efficiencies and policy formulation, thus supporting livelihoods and economic resilience in livestock-dependent communities.